Caffeine and energy drinks - Hoffman, J. R. (Strength and Conditioning Journal, 2010)
Recent research has indicated that energy drinks are the most popular supplement besides multivitamins in the American adolescent and young adult population. More than 30% of all American male and female adolescents use these supplements on a regular basis. Energy drinks are also reported to be the most popular supplement (41.7% of the 403 athletes surveyed) among young (17.7 ± 2.0 years) elite British athletes. The primary reason for their use is thought to be related to a desire for reducing or controlling body fat. However, many competitive athletes also use these energy drinks for their potential ergogenic effect. The basic active ingredient in these energy drinks is caffeine, and although ergogenic benefits have been seen with caffeine supplementation in doses ranging from 3 to 9 mg·kg-1 (equivalent to approximately 1.5-3.5 cups of automatic drip coffee in a 70-kg person), there does appear to be a difference in the ergogenic potential when caffeine is ingested in a food source (coffee or sports drink) compared with its anhydrous form. Although both forms have been shown to provide an ergogenic effect, the magnitude of performance improvements appears to be greater when caffeine is ingested in tablet form. To maximize the effectiveness of caffeine in an energy drink, supplement companies will often add several additional ingredients to exacerbate the stimulatory potential of caffeine. This brief review will examine the efficacy of these energy drinks regarding performance improvements and metabolic enhancement. In addition, issues relating to the safety of energy drink consumption will also be discussed.